2021
DOI: 10.3389/fimmu.2021.609319
|View full text |Cite
|
Sign up to set email alerts
|

JQ1 as a BRD4 Inhibitor Blocks Inflammatory Pyroptosis-Related Acute Colon Injury Induced by LPS

Abstract: Endotoxemia is a severe inflammation response induced by infection especially bacterial endotoxin translocation, which severely increases mortality in combination with acute colon injury. Bromodomain-containing protein 4 (BRD4) is an important Bromo and Extra-Terminal (BET) protein to participate in inflammatory responses. However, it is still unknown about the specific connection between BRD4 and inflammation-related pyroptosis in endotoxemia colon. Here, through evaluating the mucous morphology and the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…In this study, our data showed that canonical pyroptosis pathway exist in our model, and the patient's immunohistochemical results are also in line with expectations. When BRD4 was inhibited, NLRP3/Caspase-1/GSDMD are all decreased, which is similar to the previous study: JQ1 inhibits BRD4 and reduces the LPS-induced acute colon injury by NLRP3/ASC/Caspase-1 inflammatory pyroptosis composition (Chen et al, 2021). Of interest, BRD4 might not participate in the activation of NLRP3 in bone marrow-derived macrophages (BMDMs), but it is an important regulator for the NLRC4 inflammasome activation in response to S. typhimurium infection.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, our data showed that canonical pyroptosis pathway exist in our model, and the patient's immunohistochemical results are also in line with expectations. When BRD4 was inhibited, NLRP3/Caspase-1/GSDMD are all decreased, which is similar to the previous study: JQ1 inhibits BRD4 and reduces the LPS-induced acute colon injury by NLRP3/ASC/Caspase-1 inflammatory pyroptosis composition (Chen et al, 2021). Of interest, BRD4 might not participate in the activation of NLRP3 in bone marrow-derived macrophages (BMDMs), but it is an important regulator for the NLRC4 inflammasome activation in response to S. typhimurium infection.…”
Section: Discussionsupporting
confidence: 90%
“…BRD4 plays a vital role in aggravating acute gouty arthritis by regulating NF-kB/NLRP3/gasdermin D (GSDMD) signaling pathway (6). In addition, BRD4 accelerates colonic injury during endotoxemia, a serious inflammation response related to infection (7). Complete Freund's adjuvant (CFA) -induced inflammatory pain increases the expression of BRD4, ultimately resulting in enhanced excitability of nociceptive neurons and thermal hyperalgesia (8).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these important studies related to the NLRP3 inflammasome, the potential mechanism of GSDMD-induced pyroptosis in inflammatory pain remains unknown. BRD4 aggravates many pathophysiological activities through GSDMD-induced pyroptosis (7,17). However, the relationship between BRD4 and pyroptosis in inflammatory pain remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…BRD4 protein is a member of the bromodomain and extra-terminal domain (BET) family, that recognizes and binds to acetylated lysines in histones and non-histone proteins [ 83 ]. In several pathological mouse models in which NLRP3 inflammasome activation plays an essential role in the development and progression of the disease, blockage of BRD4 with pharmacological treatments (JQ1) or specific silencing reduces the production of inflammatory cytokines (IL-6, IL-1β, and IL-18) and pyroptosis [ 84 , 85 , 86 , 87 ]. Inhibition of BRD4 suppresses inflammasome activation by modulating NF-κB signaling, reducing the expression of all NLRP3 inflammasome components, and increasing the autophagy.…”
Section: Epigenetic Dynamics In the Expression Assembly And Activation Of The Nlrp3 Inflammasomementioning
confidence: 99%
“…For example, intestinal barrier dysfunction produces the bacterial translocation of microbial components such as LPS that goes on to activate the NLRP3 inflammasome, which contributes to the inflammation of the colon. Pre-treatment with the BET protein inhibitor, JQ1, protects the colon tight junction and inhibits NF-kB activation and NLRP3/ASC/caspase-1 expression in a mouse model of endotoxemia induced by LPS [ 85 ]. Likewise, the cleavage of gasdermins was also blocked by JQ1, regulating the cell death of colon cells.…”
Section: Epigenetic Targeting Of the Nlrp3 Inflammasomementioning
confidence: 99%